Morphology of the thoracolumbar spine of the middle Miocene hominoid Nacholapithecus kerioi from northern Kenya. Issue 88 (November 2015) - Kikuchi, Yasuhiro; Nakatsukasa, Masato; Nakano, Yoshihiko; Kunimatsu, Yutaka; Shimizu, Daisuke; Ogihara, Naomichi; Tsujikawa, Hiroshi; Takano, Tomo; Ishida, Hidemi
Abstract: A new caudal thoracic and a new lumbar vertebra of Nacholapithecus kerioi, a middle Miocene hominoid from northern Kenya, are reported. The caudal thoracic vertebral body of N. kerioi has a rounded median ventral keel and its lateral sides are moderately concave. The lumbar vertebral body has an obvious median ventral keel. Based on a comparison of vertebral body cranial articular surface size between the caudal thoracic vertebrae in the present study and one discussed in a previous study (KNM-BG 35250BO, a diaphragmatic vertebra), N. kerioi has at least two post-diaphragmatic vertebrae (rib-bearing lumbar-type thoracic vertebrae), unlike extant hominoids. It also has thick, rounded, and moderately long metapophyses on the lumbar vertebra that project dorsolaterally. The spinous process bases of its caudal thoracic and lumbar vertebrae originate caudally between the postzygapophyses, as described previously in the KNM-BG 35250 holotype specimen. In other words, the postzygapophyses of N. kerioi do not project below the caudal border of the spinous processes, similar to those of extant great apes, and unlike small apes and monkeys, which have more caudally projecting postzygapophyses. Nacholapithecus kerioi has a craniocaudally expanded spinous process in relation to vertebral body length, also similar to extant great apes. Both these spinous process features of N. kerioi differ from those of Proconsul nyanzae . The caudal thoracic vertebra of N. kerioi has a caudally-directed spinous process, whose tip is tear-drop shaped. These features resemble those of extant apes. The morphology of the spinous process tips presumably helps vertebral stability by closely stacking adjacent spinous process tips as seen in extant hominoids. The morphology of the spinous process and postzygapophyses limits the intervertebral space and contributes to the stability of the functional lumbar region as seen in extant great apes, suggesting that antipronograde activity was included in the positional behavior of N. kerioi .